Hygiene and Sanitation Challenge for COVID-19 Prevention in Indonesia - Purnama, Sang Gede; Susanna, Dewi (Kesmas, 2020)
The case of COVID-19 in Indonesia continues to increase, transmitted directly and indirectly. Hygiene and sanitation approaches are needed for prevention. The purpose of this review is to review how the transmission COVID-19, the challenges of Indonesia, and the policy of COVID-19 prevention with hygiene and sanitation approaches. The results show Indonesia's challenges namely urban area density, air pollution, and smokers, low hand washing habits, low ac- cess to clean water and drinking water, open defecation behavior, limited personal protective equipment. COVID-19 control policy with the hygiene sanitation approach is carried out with 4 factors namely personal protect equipment, health education, personal hygiene, and sanitation.